Microbiological and behavioral determinants of genital HPV infections among adolescent girls and young women warrant the need for targeted policy interventions to reduce HPV risk - Onywera, Harris; Mabunda, Sikhumbuzo A.; Williamson, Anna-Lise; Mbulawa, Zizipho Z. A. (Frontiers in Reproductive Health, 2022)
Genital human papillomavirus (HPV) is the most common sexually transmitted virus in most populations globally. Adolescent girls and young women (AGYW) remain a key population group at risk for HPV infection. However, the risk factors of HPV infection among AGYW, especially in sub-Saharan Africa, are a subject of little investigation in published literature. Here, we investigated the factors associated with HPV infection among unvaccinated South African AGYW with a high HPV burden (prevalence: 76.1%). We retrospectively recruited 213 AGYW learners (aged 15 to 25 years) from a previous cross-sectional study, the HPV Education Intervention Study, conducted in the Eastern Cape, South Africa. Sexually transmitted infections (STIs), bacterial pathobionts, genital ulcers (due to infectious causes), candidiasis, and bacterial vaginosis (BV) in the self-collected vaginal specimens were determined using the AllplexTM Panel Assays. Statistical analyses were performed using STATA v16.1. Continuous and categorical variables were computed by t-test/Wilcoxon rank-sum test and Chi-square/Fisher’s exact tests, respectively. Logistic regression was used to determine the univariable predictors of HPV infection. The overall detection rate of any viral STI, bacterial STI, pathobiont, genital ulcer, candidiasis, and BV among the AGYW was 75.0%, 34.4%, 90.7%, 14.4%, 26.9%, and 43.6%, respectively. The main factors associated with HPV infection were alcohol consumption (p-value = 0.005), infection with any and multiple Candida species (p-values = 0.011 and 0.006, respectively), Candida albicans infection (p-value = 0.010), Ureaplasma urealyticum pathobiont infection (p-value = 0.044), BV-associated bacteria (specifically Atopobium vaginae: p-value = 0.039, BV-associated bacteria 2: p-value = 0.021, Gardnerella vaginalis: p-value = 0.021, Megasphaera type 1: p-value = 0.037), and BV (p-value = 0.011). Our study, albeit not necessarily generalisable, found social behaviour as well as specific vaginal microbes as correlates of HPV infection among AGYW in South Africa. There is a need to investigate HPV epidemiology in other AGYW populations. The factors associated with genital HPV infection among AGYW burdened with HPV infection necessitate the need to formulate and implement population-specific public health strategies for creating HPV awareness and reducing its risk.